Biblioterapia: vivência e percepções dos voluntários do projeto de extensão Turma da leitura. - PAES, Priscila Silva (2021)
Study on bibliotherapy consists of in the use of reading for therapeutic purposes. Objective, in general level, to raise bibliotherapeutic concepts in hospital scope in order to use the reading to make it humanized and welcoming; and at a specific level aims to: a) raise concepts of cognitive processes to understand how reading and emotion interfere with medical treatment; b) to analyze the role of the librarian as mediator of the bibliotherapy and objective c) intended to with the intention of discussing the difficulties and strategies of the application of the sessions of bibliotherapy experienced in the hospital. It is characterized as an exploratory and qualitative research. A questionnaire applied to the volunteers of the Reading (TL). It found used as a research tool. It was observed that most of the volunteers participated in the research for about one year and attended two interns per session. During the sessions, difficulties were detected such as the lack of motivation of inmates complicating the activity, but that volunteers joked around and acquired the confidence to attract attention and apply the bibliotherapy. It is concluded that despite the diversities, the bibliotherapy is still an alternative to alleviate the suffering of the patients and to encourage the reading in people who have few conditions of access to bibliographic materials.